Rancang Bangun Robot Pelayan Pasien Berbasis Internet of Things (Iot) - Amrulloh, Saichu; Wardana, Humaidillah Kurniadi (Universitas Trunojoyo Madura, 2022)
The use of technology in the industrial revolution era and society is growing rapidly, especially the use of robots in facilitate human work. The function of robots is not only in the industrial world, but also in the world of health, for example robots to assist in serving patients. In supporting service activities in the robotic-based health world, a medical service robot design was made which aims to help reduce the duties of medical waiters while reducing the effects of COVID-19 transmission and analyze the results of designing and monitoring systems on medical service robots. The research method used is in the form of control testing and monitoring of medical service robots from the results of non-contact body temperature sensor measurements using a design tool that was made compared to standard measuring instruments and then calculating the percentage error of the measurement, hand sanitizer sensor reading distance, and connectivity esp32 cam, esp32 dev and camera 360 with wifi as well as connection time of esp32cam, esp32dev and camera 360 with wifi. The results of the measurement of the body temperature sensor have an error presentation rate ranging from 0.002% - 0.023%, the infrared sensor distance measurement reaches 14 cm and the robot connectivity distance gets good results with a distance of 505 cm, the connectivity speed of esp32 and IP cameras depends on the wifi speed used best results in this trial at 45 ms.